Development of the Saribu Rumah Gadang Tourism Area by the Tourism and Culture Office of South Solok Regency in Enhancing Minang Culture: Pengembangan Kawasan Wisata Saribu Rumah Gadang oleh Dinas Pariwisata dan Kebudayaan Kabupaten Solok Selatan Dalam Peningkatan Budaya Minang - Ira ramadani; Jumiati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Saribu Rumah Gadang Tourist Area offers a captivating cultural tourism experience, with the diversity of Rumah Gadang architecture based on ethnic groups adding to its appeal for visitors. This research aims to analyze the development of the Saribu Rumah Gadang tourist area in Solok Selatan (Solsel) in enhancing Minangkabau culture. This study uses a qualitative approach with descriptive methods, literature review, as well as interviews, observations, and documentation. The findings reveal that the development of the Saribu Rumah Gadang tourist area has not been fully optimized. Financial feasibility has not met expectations due to uneven budget allocation among the community; however, socio-economic and regional feasibility shows a positive impact on increasing local income, particularly for homestay owners and small business owners. Technical feasibility is still lacking, as evidenced by neglected facilities. Environmental feasibility is satisfactory and adequate, supported by appropriate facilities.